2022
DOI: 10.21203/rs.3.rs-1677859/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Detection of chlorfenapyr resistance in the malaria vector Anopheles gambiae contrasts with full susceptibility in Anopheles funestus across Africa

Abstract: New insecticides have recently been produced to help control pyrethroid-resistant malaria vectors including the pyrrole chlorfenapyr. Monitoring the susceptibility of mosquito populations against novel insecticides and potential cross-resistance with current insecticides is vital for better resistance management. In this study, we assessed the resistance status of the major malaria vectors Anopheles gambiae and Anopheles funestus to chlorfenapyr across Africa and explored potential cross-resistance with known … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…Such negative association noticed in this study could be attributed to the chlorfenapyr component in interceptor G2 as reported previously (44). This insecticide is considered as pro-insecticide that is activated by oxidase enzymes suggesting a potential for negative cross-resistance (45) as shown recently that mosquitoes bearing the 1014F-resistant allele were more vulnerable to chlorfenapyr (33) and clothianidin (46). The negative association observed between the kdr-resistant marker here and IG2 e cacy indicates that this tool could help control kdr-resistant mosquitoes as observed in Benin (26).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Such negative association noticed in this study could be attributed to the chlorfenapyr component in interceptor G2 as reported previously (44). This insecticide is considered as pro-insecticide that is activated by oxidase enzymes suggesting a potential for negative cross-resistance (45) as shown recently that mosquitoes bearing the 1014F-resistant allele were more vulnerable to chlorfenapyr (33) and clothianidin (46). The negative association observed between the kdr-resistant marker here and IG2 e cacy indicates that this tool could help control kdr-resistant mosquitoes as observed in Benin (26).…”
Section: Discussionsupporting
confidence: 84%
“…The high e cacy of IG2 should be therefore attributed to the chlorfenapyr component in this net as reported in many African countries a full susceptibility of An. funestus to this insecticide (33). This new net having a mixture of chlorfenapyr and alphacypermethrin showed also a better e cacy compared to Interceptor ® having only alphacypermethrin and a chlorfenapyr-only net against pyrethroid-resistant An.…”
Section: Discussionmentioning
confidence: 89%
“…funestus s.l. to this insecticide [ 37 ]. This new net having a mixture of chlorfenapyr and alphacypermethrin showed also a better efficacy compared to Interceptor ® having only alphacypermethrin and a chlorfenapyr-only net against pyrethroid-resistant An.…”
Section: Discussionmentioning
confidence: 99%
“…Such negative association noticed in this study could be attributed to the chlorfenapyr component in interceptor G2 as reported previously [ 48 ]. This insecticide is considered as pro-insecticide that is activated by oxidase enzymes suggesting a potential for negative cross-resistance [ 49 ] as shown recently that mosquitoes bearing the 1014F-resistant allele were more vulnerable to chlorfenapyr [ 37 ] and clothianidin [ 50 ]. The negative association observed between the kdr -resistant marker here and Interceptor G2 efficacy indicates that this tool could help control kdr -resistant mosquitoes as observed in Benin [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…gambiae, An. funestus resistance to insecticides has been less extensively investigated, though there is now evidence of resistance to the multiple classes of insecticides (Coetzee & Koekemoer, 2013;Knox et al, 2014) with the exception of chlorfenapyr (Tchouakui et al, 2022(Tchouakui et al, , 2023 and the neonicotinoid clothianidin, which was recently prequalified by World Health Organisation (WHO) for IRS (Fouet et al, 2020). In West Africa, An.…”
Section: Introductionmentioning
confidence: 99%